Decomposition and changes in chemical composition of leaf litter of five dominant tree species in a West African tropical forest - GUENDEHOU, GHISLAIN HIPPOLYTE SABIN; LISKI, J.; TUOMI, M.; MOUDACHIROU, MANSOUROU; SINSIN, Brice; MÄKIPÄÄ, R. (My University, 2014)
The objective of the research was to study the rate of decomposition and changes in the chemical characteristics in the leaf litter of selected tree species using a litterbag experiment. The decomposition of leaf litter from five dominant tree species, Afzelia africana, Anogeissus leiocarpa, Ceiba pentandra, Dialium guineense, and Diospyros mespiliformis was studied in the Lama forest reserve, a tropical vertisol forest in Benin. Changes in litter mass and organic compounds, including acid-hydrolysable (AH), water-soluble (WS) and ethanolsoluble (ES) compounds and Klason lignin, were determined every 4 weeks over 6-months period. The carbon (C), nitrogen (N), organic matter (OM) and ash contents of fresh litter were also determined. The high differences in the initial litter quality across the species resulted in a large variation of the absolute decay rate (ka values), ranging from 1.69 to 4.67 year-1. The key chemical controls of leaf decomposition were the initial concentrations of AH, lignin and N. The specific decay rates (ks values) of AH, WS, ES and Klason lignin varied significantly within and across species and described leaf litter as composed of labile and recalcitrant C pools having different decay patterns. WS and ES had the highest ks values of 4.65 to 11.96 year-1 and 4.06 to 21.27 year-1, respectively, whereas AH had ks values of 1.14 to 4.74 year-1 and seemed to impose its decay pattern on the whole litter. The results supported the hypothesis that litter chemistry was the main factor controlling the decomposition process at a local scale.
Keywords: Decay rate; litter quality; litterbag experiment; tropical forest.